A two-week, double-blind, placebo-controlled trial of Viola odorata, Echium amoenum and Physalis alkekengi mixture in symptomatic benign prostate hyperplasia (BPH) men - Fatemeh Beiraghdar; Behzad Einollahi; Alireza Ghadyani; Yunes Panahi; Abbas Hadjiakhoondi; Mahdi Vazirian; Ali Salarytabar; Behrad Darvishi (Taylor & Francis Group, 2017)
Context: As an alternative approach, administration of phytotherapeutic agents in management of benign prostate hyperplasia (BPH), is rapidly growing each day. Different authors have indicated effectiveness of Viola odorata L. (Violaceae), Echium amoenum Fisch. & C.A.Mey. (Boraginaceae) and Physalis alkekengi L. (Solanaceae) in treatment of BPH. However, none have reported the beneficial outcomes of the mixture yet. Objective: This study evaluates the therapeutical effects of V. odorata, E. amoenum and P. alkekengi mixture on symptomatic BPH patients. Materials and methods: Eighty six symptomatic BPH patients with International Prostate Symptom Score (IPSS) of more than 13 and prostate volume of more than 30 cm3 were randomly allocated to receive a two-week course of placebo (control group) or 1 mL of mixed hydro-alcoholic solution of P. alkekengi, E. amoenum and V. odorata extracts (1.5, 1 and 1.5% respectively) (treatment group). Results: IPSS score of incomplete urination (42.3 ± 2.04%), frequency of urination (20.08 ± 1.02%), intermittency (40.78 ± 2.16%), urgency (60.91 ± 3.14%), weak stream (50.58 ± 2.14%), straining (55.67 ± 2.53%) and nocturia (40.14 ± 1.89%) in treatment group were significantly decreased after treatment compare to placebo receiving group. Furthermore, the prostate volume (16.92 ± 0.89%) and extant urine volume (28.12 ± 1.36%) also significantly decreased in treatment group compared to control group. No significant side effects or abnormalities in biochemical tests and urinalysis were observed throughout the study. Discussion and conclusions: Based on results, mentioned mixture is safe and effective in improving life quality of patients suffering from BPH.